1995
DOI: 10.1177/001440299506100605
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Education and Inclusion of Students with Disabilities: A Delphi Investigation

Abstract: This article reports on a survey of 37 educators regarding future directions in the education of students with disabilities. The survey used the Delphi technique. For the decade of the 1990s and after the year 2000, respondents' predictions included the following: The movement toward increasing inclusion will occur; the belief will prevail that people with disabilities have a right to participate in inclusive environments; students with mild disabilities will be educated in general classrooms; teachers will in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 11 publications
0
45
0
1
Order By: Relevance
“…Putman, Spiegel. and Bruininks [29] found consensus to be reached with 80% agreement falling within two measures of a five-point Likert scale.…”
Section: Level Of Consensusmentioning
confidence: 84%
“…Putman, Spiegel. and Bruininks [29] found consensus to be reached with 80% agreement falling within two measures of a five-point Likert scale.…”
Section: Level Of Consensusmentioning
confidence: 84%
“…Both the faculty and the school became more confident about referring students because they had heard of the LADS program at the end of 2007, and maintained this confidence in the use of LADS into 2008. Moreover, the information gained from the LADS was used to inform faculty staff (with the student's permission), and students with SLD appeared to improve their learning capabilities as they felt faculty were well advised [34,35].…”
Section: Key Stakeholdersmentioning
confidence: 99%
“…In a recent study on future directions in the education of students with disabilities, Putnam, Spiegel, & Bruininks (1995) indicated that ?movement toward inclusion will continue, and the belief will predominate that people with disabilities have the right to full participation in integrated settings and activities (p.572). Presumably, this includes disabled students' interaction with the academic content in the regular education curriculum.…”
Section: Emerging Themes: Major Dilemmasmentioning
confidence: 99%